Millimeter-Wave Radio-over-Fiber Links based on Mode-Locked Laser Diodes - Brendel, Friederike (Karlsruher Forschungsberichte aus dem Institut für Hochfrequenztechnik und Elektronik, 2013)
Radio communications in the range of 60 GHz enable multi-Gigabit/s network access in indoor environments. Due to the propagation characteristics of such signals only very short range radio transmission is feasible. In order to distribute these signals across large distances, analog transmission over optical fiber is considered. In this work, mode-locked laser diodes serve as optoelectronic oscillators for the generation of such signals. Their system-relevant properties are studied in detail.